Optimization of Growth Conditions to Produce Sustainable Polyhydroxyalkanoate Bioplastic by Pseudomonas aeruginosa EO1 - Mahato, Richa Prasad; Kumar, Saurabh; Singh, Padma (Frontiers in Microbiology, 2021)
Polyhydroxyalkanoates (PHAs) are intracellularly synthesized by bacteria as carbonosomes that exhibit biodegradable thermoplastics and elastomeric properties. The use of cheaper edible oils as a source of carbon assists in the reduction of the production cost of such biopolyesters. In this work, different edible oils, such as groundnut oil (GNO), mustard oil, sesame oil, and soybean oil (SBO) were used to check their effect on PHA production from Pseudomonas aeruginosa EO1 (MK049902). Pseudomonas aeruginosa EO1 was used in a two-stage production system. In the first stage, bacterial growth was favored and, in the second, PHA was synthesized. GNO was found as the best carbon source for PHA production. The use of 2% (v/v) GNO, rich in saturated fatty acids, allowed PHA content of 58.41% and dry cell weight (DCW) of 10.5g/L at pH7 and temperature 35°C for 72h. Groundnut has a high potential for oil production and for the diversification of co-products with some potential of value aggregation. Such a perennial and sustainable species will almost certainly meet the criteria for becoming a significant commercial oilseed crop. Fourier transform infrared spectroscopy (FTIR) spectra showed strong characteristic bands at 1,282, 1,725, 2,935, 2,999, and 3,137cm−1 for the PHA polymer. Gas chromatography-mass spectrometry (GC-MS) detects the presence of PHA copolymers.